2017
DOI: 10.1017/s1355617717000935
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychosocial Factors and Cognition in Ethnically Diverse Older Adults

Abstract: Results confirm and extend the link between self-efficacy and cognition in late life, particularly for White and Black older adults. Previous studies on positive psychosocial factors in cognitive aging may not be generalizable to Hispanics. Longitudinal follow-up is needed to determine whether negative relationships between certain psychosocial factors and cognition in Hispanics reflect reverse causation, threshold effects, and/or negative aspects of having a strong social network. (JINS, 2018, 24, 294-304).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 42 publications
7
33
3
1
Order By: Relevance
“…Older adults can enjoy close communication, interaction, and companionship of neighbors and generate positive emotions, friendship and a sense of meaning and reduce their loneliness. Studies have shown that these positive emotions can help prevent depressive symptoms in the elderly [43,44].…”
Section: Association Between Functional Disability and Depressive Symmentioning
confidence: 99%
“…Older adults can enjoy close communication, interaction, and companionship of neighbors and generate positive emotions, friendship and a sense of meaning and reduce their loneliness. Studies have shown that these positive emotions can help prevent depressive symptoms in the elderly [43,44].…”
Section: Association Between Functional Disability and Depressive Symmentioning
confidence: 99%
“…However, fewer epidemiological studies have considered the effects of positive psychosocial factors on cognitive aging outcomes. In previous cross-sectional studies, we documented positive associations between cognitive functioning and both self-efficacy and social support above and beyond other negative and positive psychosocial factors (Zahodne, Nowinski, Gershon, & Manly, 2014;Zahodne, Watson, Seehra, & Martinez, 2018). While longitudinal evidence is even more scarce, available data from the MacArthur Studies of Successful Aging support a prospective association of both self-efficacy and social support with later cognitive performance (Seeman, Lusignolo, Albert, & Berkman, 2001;Seeman, McAvay, Merrill, Albert, & Rodin, 1996).…”
Section: Introductionmentioning
confidence: 62%
“…Such detailed information is needed to determine the specificity and potential generalizability of effects, which is critical if the ultimate goal is to target specific positive psychosocial factors for prevention or intervention research in cognitive aging. For example, cross-sectional associations between certain positive psychosocial factors (e.g., social support) and cognition may differ across racial and ethnic groups (Zahodne et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive intervention will include restorative and compensatory cognitive stimulation, learning mnemonics strategies and music therapy, and will be carried out by two trained psychologists and a music therapist. Intervention will use a metacognitive and a motivational approach applied to subjects with MCI, as described in previous studies [43,44]. Participants will be also required to perform home exercises, which will include some cognitive stimulation exercises, assigned at the end of each class.…”
Section: Interventionmentioning
confidence: 99%